MANAJEMEN PEMBELAJARAN TILAWATIL QURÔÇÖAN DI SD NEGERI SUMBERSALAK 01 KECAMATAN LEDOKOMBO KABUPATEN JEMBER - jurnalmap map; Nur Kholifah; Subijanto ÔÇÄ (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2020)
The objectives of this study are to describe the planning of Tilawatil Qur'an learning, implementation of Tilawatil Qur├ín learning, and evaluation of Tilawatil Qur'an learning in Sumbersalak 01 Primary School, Ledokombo District, Jember Regency. The method used in this research is descriptive qualitative. The subjects in this study is the Tilawatil Qur'an teachers while the informants of this study are the Principal, Deputy Principal, Islamic Religious Teachers, Tilawatil Qur'an Teachers. The results of this study are: (1) Tilawatil Qur'an Learning Planning in Sumbersalak 01 Elementary School Ledokombo Subdistrict, Jember Regency does not use the Syllabus and Learning Implementation Plan (RPP) but instead uses the reading target prepared by Tilawatil teachers, Islamic religion teachers, deputy head schools and school principals through coordination meetings. This Tilawatil Qur'an study is included in local content subjects. (2) The implementation of Tilawatil QurÔÇÖan Learning at Sumbersalak 01 Elementary School, Ledokombo Subdistrict, Jember Regency is carried out through two stages, namely the stage before learning and the core stage of learning. The method used is the Jama'i and talaqqi methods. Learning takes place on the first hour of Friday and at the extracurricular hour. The media used are the Qur'an and the book recitation. (3) Evaluation of ur Tilawatil learning conducted at SD Sumbersalak 01 District Ledokombo, Jember Regency uses an assessment in the form of a reading deposit system.Keywords: learning, Tilawati QurÔÇÖan